Contrastive Analysis Study of Nominalization in 2024 Indonesian Presidential Candidates' Speeches - Yulianti, Deni Friska; Oktoviandry, Rifki (English Language and Literature, 2024)
This study aims to find the types and differences in nominalizations used in the speeches of the 2024 Indonesian presidential candidates: Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. Using data from a YouTube video hosted by CSIS Indonesia titled "Pidato Calon Presiden Republik Indonesia: Arah dan Strategi Politik Luar Negeri," which aired from November 7th to November 13th, 2023, the analysis reveals key linguistic strategies. Anies Baswedan employs 90 nominalizations with a balanced distribution between deverbal (41%) and deadjectival (59%) types. In contrast, Ganjar Pranowo uses 89 nominalizations, favouring deverbal types (42%) over deadjectival (58%). Anies Baswedan and Ganjar Pranowo analyze the frequency and percentage of different affixation types in their respective languages. Anies Baswedan has the most frequent affixation, "Ke-an," with 57% of the total. In contrast, English nominalization categorizes affixation to determine types, such as deverbal and deadjectival, using suffix affixation processes. Indonesian nominalization, however, lacks such categorization, relying solely on the base word formed. These findings provide insights into the distinct linguistic styles and rhetorical preferences of the candidates.